2004
DOI: 10.1074/jbc.m408581200
|View full text |Cite
|
Sign up to set email alerts
|

Two Homologous Apolipoprotein AI Mimetic Peptides

Abstract: Two related 18-amino acid, class A, amphipathic helical peptides termed 3F-2 and 3F 14 were chosen for this study. Although they have identical amino acid compositions and many similar biophysical properties, 3F-2 is more potent than 3F 14 as an apolipoprotein AI mimetic peptide. The two peptides exhibit similar gross conformational properties, forming structures of high helical content on a membrane surface. However, the thermal denaturation transition of 3F-2 is more cooperative, suggesting a higher degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In addition, the effect of 3F 14 is somewhat greater close to the end of the acyl chain but before the terminal methyl group. These results are consistent with 1 H MAS/ NOESY measurements that demonstrated that in pure POPC 3F 14 inserted deeper into the membrane than 3F-2 and that cholesterol inhibited the entry of both peptides into the membrane (26).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the effect of 3F 14 is somewhat greater close to the end of the acyl chain but before the terminal methyl group. These results are consistent with 1 H MAS/ NOESY measurements that demonstrated that in pure POPC 3F 14 inserted deeper into the membrane than 3F-2 and that cholesterol inhibited the entry of both peptides into the membrane (26).…”
Section: Discussionsupporting
confidence: 81%
“…observations is that the active peptide 3F-2, due to -electrons at the center of the nonpolar face (that results in a trapezoidal cross-sectional shape), is not able to bury deeply within the lipid acyl chains (26).…”
Section: Discussionmentioning
confidence: 99%
“…Each of these substances was added to 50 M LUV of DOPC:cardiolipin (2:1) or DOPC:DOPE:cardiolipin (1:1:1) to give a final concentration of additive of 7 M. After the addition of Ca 2ϩ and 40 nM tBid (twice the concentration used to obtain the data of Fig. 1), leakage reached a value of 10% or less of the total contents, over the first 200 s. We also tested cyclosporin A, an immunosuppressive peptide that inhibits processes requiring negative curvature (30). At a concentration of 10 M this peptide completely inhibited leakage from DOPG/DOPC/DOPE (1:1:1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the membranes of mitochondria of amoeba form structures resembling a lipidic cubic phase, a structure formed by membranes with negative curvature propensity (29). The morphological reorganization of mitochondria observed during apoptosis is inhibited by cyclosporin A (28), a peptide that has been shown to inhibit membrane processes requiring increased negative curvature (30). Furthermore, ceramides, a class of lipids that promotes negative curvature (31), cause the release of cytochrome c from isolated mitochondria (32)(33)(34).…”
mentioning
confidence: 99%
“…We have shown previously that the two homologous apoA-I mimetic peptides, 3F-2 and 3F 14 , differ in their in vitro antiatherogenic properties (50), and the peptide 3F-2 inhibits atherosclerosis in female apoE null mice, whereas 3F 14 does not (51). Using several NMR methods, we have shown that these two peptides insert to different extents into lipid vesicles (51).…”
Section: Peptide 4f Interacts With the Lipid Acyl Chains And Orientedmentioning
confidence: 99%